Nusajaya towards a metropolitan housing : in conjuction with the Iskandar development region - 465618 Leong, Ai Mei; Mohd. Tajuddin Mohd. Rasdi; Fakulti Alam Bina (2008)
Project Paper (Sarjana Muda (Senibina)) - Universiti Teknologi Malaysia, 2008